1994
DOI: 10.1111/j.1600-0897.1994.tb00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Antisperm Antibodies in Infertile Men

Abstract: The prevalence of ASAs in this population was 14%, while the prevalence of the control group was 2.5%. Of all factors analyzed only a history of vasectomy, an acute epididymitis, and an abnormal result in the bovine mucus penetration test was associated with elevated ASA titers (P < .001). In addition, we could demonstrate a time related formation of ASAs in men after vasectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
72
1
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 44 publications
2
72
1
4
Order By: Relevance
“…This is probably a rejection mechanism, since the presence of antisperm antibodies has been associated with impaired fertility. Heidenreich et al [21] have demonstrated that the prevalence of antisperm antibodies in the general population is 0-5%, and a higher prevalence in infertile men at 7-26%. The main hypothesis of the present study was that ABO blood group status and combination between spouses may be a factor in the expression of circulating antisperm antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably a rejection mechanism, since the presence of antisperm antibodies has been associated with impaired fertility. Heidenreich et al [21] have demonstrated that the prevalence of antisperm antibodies in the general population is 0-5%, and a higher prevalence in infertile men at 7-26%. The main hypothesis of the present study was that ABO blood group status and combination between spouses may be a factor in the expression of circulating antisperm antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that promote the production of antisperm antibodies include infection [2], trauma and smoking [12,21]. We have recently reported an association between antisperm antibody production and HLA haplotypes DR4, DR6, and DQw3 in women and DR6 and DQ7 in men, and homozygosity of DR4, DR6, and DQ7 was more common in couples with antisperm antibodies but deficient in DQw3 [22].…”
Section: Discussionmentioning
confidence: 99%
“…However ASA may also be present in both fertile men and women [14,15]. This indicates that not all ASA cause infertility and their role in reproduction remains questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Among the risk factors for ASA production, the chronic inflammatory diseases with different localization are believed to play an important role [5][6][7][8]. The inflammatory response is associated with production of antibodies to spermatozoal and microbial antigens.…”
Section: Introductionmentioning
confidence: 99%